Uncertainties in Earthquake Risk Assessment for Disaster Planning - Yasin Fahjan; Ferhat Pakdamar; Yaşasın Eryılmaz; Fatma Kara (Doğal Afetler ve Çevre Dergisi)
To obtain the sustainability of social life and to increase resistance to disaster that cause loss of life and properties; it is possible to raise awareness in the community about disaster preparedness and engross to take all the components. Disaster planning is an approach that targets the correct use of resources to decrease negative impacts in the community after the disaster. In Turkey, earthquake losses have an important role in disaster planning. There are two basic approaches for earthquake loss estimation used in disaster planning namely deterministic and probabilistic. Uncertainties of the seismic risk assessment parameters can be generated from ground motion computations, structural inventories and risk methodologies. In this study, uncertainties in the ground motion estimations are investigated. Gebze district that located close to major fault lines at Marmara region, and had significant damage during Kocaeli earthquake (1990), is selected as a study case for the risk assessment scenarios. The uncertainties parameters in ground motion computation that have major effect on the risk assessment are considered as earthquake source, earthquake magnitude and soil parameters. As a result, building damage ratios, loss of life and the need for shelter are computed. The soil amplification effects on the seismic intensity level and damage ratios are emphasized. The earthquake hazard estimation and risk assessment computation were performed utilizing geographic information system based software AFAD-RED. The software combines the scenario based seismic hazard procedure with the existing building inventories and soil data for the risk estimations. As a result, it is concluded that, uncertainties in ground motion computations have important effect on the seismic risk assessment and should be considered in disaster planning process.